2019
DOI: 10.1007/s12630-019-01409-5
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of McGrath MAC videolaryngoscope, Pentax Airway Scope, and Macintosh direct laryngoscope for nasotracheal intubation in patients with manual in-line stabilization

Abstract: Background The objective of this study was to determine the clinical usefulness of videolaryngoscopes (VLs) by comparing the time to intubation (TTI) and the ease of intubation of McGrath MAC VL (MVL), Pentax Airway Scope VL (PVL), and Macintosh direct laryngoscope (DL) during nasotracheal intubation using manual in-line stabilization to simulate difficult airways. Methods One hundred and twenty patients were randomly assigned to the MVL group (n = 40), the PVL group (n = 40), and the DL group (n = 40). Nasotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…The definition of time to intubation varied from the mouth opening until the detection of ETCO 2 [ 25 , 27 , 30 ], end of mask ventilation until detection of ETCO 2 [ 26 ], intranasal placement until detection of ETCO 2 [ 28 ], insertion through nostril until detection of ETCO 2 [ 29 ], passing through the nasal cavity until chest rise [ 31 ], placement of the endotracheal tube [ 32 , 33 ], or as not clear [ 34 ]. Pooled analysis showed a significantly shorter time to intubation favoring VL (MD: −9.04, 95% CI [ –12.71, –5.36], n = 597, P < 0.001, I 2 = 59%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of time to intubation varied from the mouth opening until the detection of ETCO 2 [ 25 , 27 , 30 ], end of mask ventilation until detection of ETCO 2 [ 26 ], intranasal placement until detection of ETCO 2 [ 28 ], insertion through nostril until detection of ETCO 2 [ 29 ], passing through the nasal cavity until chest rise [ 31 ], placement of the endotracheal tube [ 32 , 33 ], or as not clear [ 34 ]. Pooled analysis showed a significantly shorter time to intubation favoring VL (MD: −9.04, 95% CI [ –12.71, –5.36], n = 597, P < 0.001, I 2 = 59%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 ). A pooled analysis of overall intubation success rates with the two types of laryngoscopes in all studies except two [ 28 , 29 ] showed no significant difference (RR: 1.04, 95% CI [0.98, 1.10], n = 411, P = 0.17, I 2 = 60%; high-quality evidence) ( Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it can be used on a limited basis because it requires experienced clinicians and takes longer to conduct than other devices. Recognition of these limitation had led to introduction of the variety of endotracheal intubation devices including various videolaryngoscopes to secure the airway for NTI in patients with cervical spine instability [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…We thank Dr. Shao et al 1 for their valuable comments on our recent article. 2 They raised important concerns and questions, which we further address below.…”
Section: To the Editormentioning
confidence: 99%